If
![a \: \times b = {a}^{2} - {b}^{2} +2ab \: \: and \: a \: \div b \: = {a }^{2} \: + {b}^{2} - 2ab.then \: what \: is \: the \: value \: of \: (2 \times 3) + (4 \div 5) a \: \times b = {a}^{2} - {b}^{2} +2ab \: \: and \: a \: \div b \: = {a }^{2} \: + {b}^{2} - 2ab.then \: what \: is \: the \: value \: of \: (2 \times 3) + (4 \div 5)](https://tex.z-dn.net/?f=a+%5C%3A++%5Ctimes+b+%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%2B2ab+%5C%3A++%5C%3A+and+%5C%3A+a+%5C%3A++%5Cdiv+b+%5C%3A++%3D++%7Ba+%7D%5E%7B2%7D++%5C%3A++%2B++%7Bb%7D%5E%7B2%7D++-+2ab.then+%5C%3A+what+%5C%3A+is+%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A+%282+%5Ctimes+3%29+%2B+%284+%5Cdiv+5%29)
?
please don't samp
Answers
Answered by
3
Answer:
a-b+c
Step-by-step explanation:
Given equation is a2−2ab−c2+b2
We can write the given equation as,
⇒ a2−2ab+b2−c2
⇒ (a−b)2−c2 ....Since (a2−2ab+b2=(a−b)2)
Also we know,
m2−n2=(m+n)(m−n)
Here, m=(a−b) and n=c
Thus a2−2ab−c2+b2=(a−b+c)(a−b−c)
Factors are (a−b+c) and (a−b−c).
Answered by
2
Answer:
hi my friend how are you I am your friend and you too I am
Similar questions